Efektivitas Program Edukasi dalam Meningkatkan Pengetahuan Orang Tua tentang Perawatan Luka Pasca Sirkumsisi Di Kelurahan Kedaton - Fitri Afdhal; Nurilaini Nurilaini; Yopania Putri; Rahma Dita; Ni Kadek Sunita Saputri; Resti Marsila; Nurul Fitri; Putri Dewi; Shelvy Andela; Patricia Octavianus; Rika Dwi Saputri; Qori Agusti; Irwansyah Irwansyah (JURNAL PENGABDIAN KADER BANGSA, 2026)
Circumcision is a common surgical procedure in male children that requires proper wound care to prevent complications such as infection and bleeding. Parental knowledge plays an important role in ensuring optimal healing. Preliminary observations in Kedaton Village indicated limited community understanding of post-circumcision wound care. This program aimed to improve knowledge through health education and free wound examinations. The intervention was conducted on February 12, 2026, involving more than 30 participants, using lectures, discussions, demonstrations, and educational posters. The results showed improved participant understanding of proper wound care techniques, early signs of infection, and the importance of regular monitoring. This health education program proved effective in increasing knowledge and has the potential to reduce post-circumcision complications.